PEMIKIRAN FIKIH KEMASLAHATAN DAN FIQIH AKHLAK (Membaca Kembali Kitab Bidâyatul Mujtahid wa Nihâyatul Muqtashid adalah karya Ibn Rusyd) - Zaenudin MA; Ibnu Rusydi (al-Afkar, Journal For Islamic Studies, 2019)
The Book of Bid?yatul mujtahid whose full title is Bidâyatul mujtahid wa nihâyatul muqtashid is the work of Ibn Rushd in the field of Jurisprudence which is the most famous and most qualified when compared to his other Jurisprudence books. Basically, the view of fiqh Ibn Rushd was no different from the previous fiqh scholars in terms of the relationship between Shari'a and benefit. What distinguishes between Ibn Rushd and the others is the emphasis. If the Jurists emphasized the benefit and interests, Ibn Rushd emphasized his views on the moral side. He believes that the Shari'a was born to improve human morals. In this case El Abidi stated that Ibn Rusyd was the only Jurist who built the objectives of the Shari'a on a moral foundation (morals). Kitab Bidâyatul mujtahid yang judul lengkapnya adalah Bidâyatul mujtahid wa nihâyatul muqtashid adalah karya Ibn Rusyd dalam bidang Fikih yang paling terkenal sekaligus paling berkualitas jika dibandingkan dengan buku-buku Fikihnya yang lain. Pada dasarnya, pandangan fikih Ibn Rusyd tidak berbeda dengan para ulama fikih sebelumnya dalam hal hubungan antara syariat dengan kemaslahatan. Yang membedakan antara Ibn Rusyd dan yang lainnya adalah penekanannya saja. Jika para ahli fikih menekankan sisi kemaslahatan dan kepentingan, Ibn Rusyd menekankan pandangannya pada sisi moral. Ia berpendapat bahwa syariat itu lahir untuk memperbaiki akhlak manusia. Dalam hal ini El Abidi menyatakan bahwa Ibn Rusyd adalah satu-satunya ahli fikih yang membangun tujuan syariat di atas fondasi moral (akhlak).